Analisis Implementasi Program Bimbingan Konseling pada Bidang Bimbingan Belajar di Kurikulum Merdeka - Yuza, Arlina; S, Neviyarni; Herawati, Susi; Darwianis, Darwianis; Wirnita, Wirnita (MODELING: Jurnal Program Studi PGMI, 2023)
The application of the learning curriculum also affects the perspectives obtained by students, both their understanding of education and the involvement of guidance and counseling in the school itself. As an inseparable part of the learning process in schools, guidance and counseling services are expected to be able to help achieve the goals of the independent curriculum. The purpose of this study was to determine the implementation of the guidance and counseling program in the field of tutoring in the independent curriculum. This research method is qualitative research with a phenomenological approach. The implementation of the counseling guidance program at SDN 03 Pakan Labuh is based on what the teacher does, namely that the teacher has carried out the function of a class teacher who is also a student counseling teacher. One of the services that teachers have provided related to the field of tutoring is to provide learning guidance services and also consulting services. However, several counseling guidance services have not been carried out related to the field of tutoring. So in this case the counseling teacher needs to pay more attention to the role they have so that the role of counseling as a profession can help the successful implementation of the independent curriculum in elementary schools.